Inappropriate Scenes and Behavior in the Cartoon Crayon Shinchan - Tumbelaka, Riga; Hestiana, Siska; Pertala, Erik Candra (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The title of this research is Inappropriate Scene and Behaviour in the Cartoon Crayon Shinchan, this research aims to show inappropriate scenes and behaviour that is being shown in this cartoon that is being watched by a lot of younger audiences in different countries but for this research, the writers are choosing on focusing on the country of Indonesia, the result of this research shows that quite a lot of scene in the cartoon of Crayon Shinchan are not suitable to show to a minor child and more toward the adult audience. Keywords: Inappropriate scene, Cartoon, Crayon Shinchan